Back-up Arteriovenous Fistulas in Peritoneal Dialysis Patients: A Systematic Review and Meta-analysis - Hicham I. Cheikh Hassan; Pauline Byrne; Christie Harrod; Donia George; Karumathil Murali; Jenny H.C. Chen; Judy Mullan (Kidney Medicine)
Rationale & Objective: Peritoneal dialysis (PD) is a dialysis modality limited by the potential need of transferring to hemodialysis. Optimal hemodialysis vascular access is an arteriovenous fistula. Back-up arteriovenous fistula (bAVF) is a strategy to prevent central venous catheter (CVC) insertion, but its use in the PD population has not been systematically reviewed. Study Design: Systematic review and meta-analysis. Setting & Study Populations: Studies including PD patients with a bAVF and the associated outcomes, including risk of hemodialysis transfer with a CVC and the proportion of bAVFs used. Selection Criteria for Studies: Retrospective or prospective, observational studies, non-randomized or randomized controlled trials. Data Extractions: Vascular access at time of hemodialysis transfer (bAVF vs CVC) for patients with and without a bAVF. The data on bAVF outcomes included bAVFs that stopped working, were never used, and the number of patients requiring hemodialysis. Analytical Approach: Random-effects meta-analysis and meta-proportional analysis were conducted, with risk of bias within studies assessed using the Newcastle-Ottawa Scale. Results: We screened 1,855 studies, 11 of which met the inclusion criteria, comprising 598 (62%) patients with a bAVF and 368 (38%) without. The proportion of bAVFs never used was 69% (95% confidence intervals [CI], 0.58-0.80; I2 = 86.2%). Meta-analysis of 8 studies found no difference in hemodialysis transfer between patients with a bAVF and those without (hazard ratio, 1.14; 95% CI, 0.86-1.51). However, the risk of hemodialysis transfer with a CVC was significantly lower in patients with a bAVF (hazard ratio, 0.43; 95% CI, 0.17-0.68). Limitations: Substantial heterogeneity between the studies and large number of studies with poor quality. Conclusions: bAVF was associated with a high rate of non-utilization but a lower risk of starting hemodialysis via a CVC. Future studies assessing long-term clinical outcomes may provide further insights into the role of bAVF creation in shaping dialysis unit policies. Plain-Language Summary: Peritoneal dialysis (PD) is limited by hemodialysis transfer. The optimal vascular access in hemodialysis is the arteriovenous fistula, yet requirements for maturation often necessitate a central venous catheter (CVC) insertion in acute transfers from PD. A back-up arteriovenous fistula (bAVF) is a strategy used to avoid CVC use in such situations. However, no consensus is currently available on the best approach for bAVF in PD. By conducting a systematic review, we found that 69% of bAVFs were never used. Nevertheless, bAVFs reduced the risk of hemodialysis transfer with a CVC by almost 60%. The studies in the review were small in number and exhibited high heterogeneity, emphasizing that further research is needed to clarify the role and benefits of a bAVF in PD patients.